Numerical Study on Effects of Arrayed Pulsed Energy Depositions on a Supersonic Combustor - Zilin Cai; Feng Gao; Hongyu Wang; Cenrui Ma (International Journal of Aerospace Engineering)
This paper proposes a method to improve the mixing efficiency of a supersonic combustor by using arrayed pulsed energy depositions, and this method is verified by a numerical simulation. In the simulation, the Navier-Stokes equations with an energy source are solved to simulate the effects of energy depositions in various distributions on the fuel mixture in the combustor. It is found that the energy deposition arranged in the streamwise direction leads to a significant improvement in the mixing efficiency and maximum concentration decay rate of the ethylene fuel by increasing the scale of the jet-induced counter-rotating vortex pair. The energy deposition arranged in the spanwise direction introduces another counter-rotating vortex pair which can also contribute to the fuel mixture. By comparison, the energy deposition distributed in the streamwise direction and downstream of the jet orifice is shown to be the most effective case in the fuel mixing enhancement. Under the energy deposition, the wall pressure on the trailing edge of the cavity is increased which leads to a decrease in the total pressure recovery of the combustor, but this decrease is not significant.